Microwave-assisted synthesis of nitrogen-doped carbon dots using prickly pear as the carbon source and its application as a highly selective sensor for Cr(vi) and as a patterning agent. Issue 3 (5th January 2022) - Bhatt, Shreya; Vyas, Gaurav; Paul, Parimal
Abstract : Nitrogen-doped fluorescent carbon dots, prepared from prickly pear and m -xylylenediamine using microwave, selectively detect Cr(vi ) in water. Sensing strips prepared from the CDs are successfully used in the field and also used as patterning agent. Abstract : Preparation of water-dispersible carbon dots from inexpensive natural carbon precursors and its application for purposes such as sensing, bio-imaging and patterning agents is showing growing interest in recent years. In this study, we have reported the preparation of nitrogen-doped carbon dots (N-CDs) using prickly pear as the carbon source and m -xylylenediamine as the nitrogen source using a one-step microwave-assisted synthetic process. The N-CDs prepared were characterized on the basis of elemental analysis, XPS, powder-XRD, FT-IR, Raman, TEM, UV-vis and fluorescence spectroscopy. Doping of nitrogen in the N-CDs made them highly fluorescent and the study on their ion-recognition property revealed that they detect highly toxic Cr(vi ) with high selectivity and sensitivity (LOD, 0.04 μM) and without interference from the other ions used in this study. By immobilizing these N-CDs onto filter paper, sensor strips were prepared for on-site monitoring/field applications and they were successfully used for the detection of Cr(vi ) in water. Detailed spectral analysis revealed that the mechanism of Cr(vi ) sensing involved a phenomenon called the "inner filter effect" and analysis of the fluorescence lifetime data suggested the "static quenching" of fluorescence intensity. These N-CDs were used to prepare fluorescent carbon ink and were successfully used as patterning agents.